GARCH models, tail indexes and error distributions: An empirical investigation - Boril Šopov; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2015)
We perform a large simulation study to examine the extent to which various generalized autoregressive conditional heteroskedasticity (GARCH) models capture extreme events in stock market returns. We estimate Hill's tail indexes for individual S&P 500 stock market returns ranging from 1995-2014 and compare these to the tail indexes produced by simulating GARCH models. Our results suggest that actual and simulated values differ greatly for GARCH models with normal conditional distributions, which underestimate the tail risk. By contrast, the GARCH models with Student's t conditional distributions capture the tail shape more accurately, with GARCH and GJR-GARCH being the top performers.
Keywords: C15; C58; G17; 330; GARCH; extreme events; S&P 500 study; tail index